Nullius The Anthropology of Ownership, Sovereignty, and the Law in India - Kapila, Kriti (HAU Books, 2022)
Nullius is an anthropological account of the troubled status of ownership in India and its consequences for our understanding of sovereignty and social relations. Though property rights and ownership are said to be a cornerstone of modern law, in the Indian case they are often a spectral presence. Kapila offers a detailed study of paradigms where proprietary relations have been erased, denied, misappropriated. The book examines three forms of negation, where the Indian state de facto adopted doctrines of terra nullius (in the erasure of indigenous title), res nullius (in acquiring museum objects), and, controversially, corpus nullius (in denying citizens ownership of their bodies under biometrics). The result is a pathbreaking reconnection of questions of property, exchange, dispossession, law, and sovereignty.